2022
DOI: 10.3390/ijerph191811380
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Fatigue among Nurses during the COVID-19 Pandemic

Abstract: This study identified clinical nurses’ fatigue and related factors during the COVID-19 pandemic. This was a cross-sectional study. Data were collected from South Korean hospitals on 234 nurses’ general characteristics, fatigue, depression, occupational stress, insomnia, and perceived daytime sleepiness using a structured questionnaire. The prevalence of fatigue was 62.0%, depression 52.1%, insomnia 20.7%, and daytime sleepiness 36.1%. Insomnia, sleepiness, depression, and occupational stress were significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 33 publications
0
13
0
2
Order By: Relevance
“… 42 In another study, the prevalence of fatigue was 62.0%, and depression was 52.1% among nurses. 23 Sagherian et al found that nurses who cared for COVID-19 patients for more than 40 hours per week had a significant risk for fatigue and psychosocial well-being. 11 A qualitative study found that ICU nurses felt physical exhaustion caused by wearing PPE, which minimized their working capacity and ability to focus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 42 In another study, the prevalence of fatigue was 62.0%, and depression was 52.1% among nurses. 23 Sagherian et al found that nurses who cared for COVID-19 patients for more than 40 hours per week had a significant risk for fatigue and psychosocial well-being. 11 A qualitative study found that ICU nurses felt physical exhaustion caused by wearing PPE, which minimized their working capacity and ability to focus.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that overtime negatively affects the health and well-being of caregivers’ quality of care. 22 , 23 Before the pandemic, Ball et al survey of nurses reported that shifts of more than 12 hours were associated with poor quality of care ratings, higher rates of care left undone, and the longer the shift, the higher the dissatisfaction level. 24 Jarrar et al examined the associations between nursing duty hour length on nurses’ reported quality and safety in Malaysian hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…The results of a grounded theory study showed that the physical environment and inappropriate arrangement of the ward were the underlying factors affecting the severity of nurses' exposure to alarm fatigue [41]. In a study conducted in South Korea, nurses experienced high fatigue related to the physical environment, which might be due to the high workload and noise [45]. Similarly, the ndings of another study showed that the more unfavorable was the work environment, the higher was the level of fatigue [46].…”
Section: Resultsmentioning
confidence: 99%
“…Studies have reported fear of social isolation, discomfort caused by protective equipment, and multiple alarms as the main factors of nurses' fatigue [47]. Providing a standardized and safe physical environment for nurses caring for patients with COVID-19 is critical for patient and nurse safety [45,47]. Therefore, nursing managers should take the necessary measures in this eld.…”
Section: Resultsmentioning
confidence: 99%
“…Poor sleep conditions, insomnia and sleepiness were found to be associated with severe fatigue [28,32,52,54,63] . A bad mood, such as anxiety and depression, was found to be associated with fatigue [23] . Lower job satisfaction was found to be associated with work-related fatigue [30,34,37,44,47,53,56] .…”
Section: Individual Acts and Conditionsmentioning
confidence: 99%